STUDENTS’ SELF-ESTEEM AND ITS CONTRIBUTION TO ENGLISH LEARNING ACHIEVEMENT - Ridwan, Ridwan; Prayatma, Andhini (Borneo Journal of English Language Education, 2021)
The purpose of this research was to find out any contribution of self-esteem to the English learning achievement of the eighth grade students of SMP Negeri 1 Tarakan. This research employed a correlational method and the eighth grade students at SMP Negeri 1 Tarakan as the population with a total of 348 students. The number of samples in this research was 186 students who were determined by using the Slovin formula with an error rate of 5%, so that 16-17 students were taken from each class and used the proportionate stratified random sampling technique. The data collection techniques in this research used a questionnaire that was distributed to the sample, an interview to representative students, and documentation which was mainly from the result of final test of the odd semester in the academic year 2020/2021. The data analysis technique in this research used descriptive analysis and regression analysis. The results of the research showed that the mean score of self-esteem was 78.45 with the percentage spread across the very high category of 3.76%, high 41.94%, moderate 34.95%, low 15.05% and very low 4.30%, while the mean score of students’ English learning achievement was 79.93 with the percentage ranged from the very good category of 6.45%, good 43.01%, fair 31.72%, to poor 18.82%. The T-test result was 0.000 which was less than 0.05 indicated that the independent variable contributed to the dependent variable. The regression equation was Y = 16.487 + 0.809, which meant the constant value of the English learning achievement was 16.487 and the self-esteem value was 0.809, where for every point increased in the self-esteem variable, the learning achievement value would increase about 0.809 point. The coefficient of determination (R2) which was 0.088 pointed out that the students’ self-esteem contributed to their English learning achievement by 88%, while other 12% were contributed by other factors which were not explored in this research. Based on these results, it can be concluded that there was a contribution of self-esteem to the English learning achievement of the eighth grade students of SMP Negeri 1 Tarakan.